"If We Lose Their Language We Lose Our History": Knowledge and Disposition in Māori Language Acquisition Policy. Issue 2 (4th March 2018) - Albury, Nathan John
ABSTRACT: Localising knowledge and dispositions helps to predict the likely success of top-down language policies. In so far as language acquisition is a pillar of language revitalisation policy, then community perspectives on learning a minority language deserve attention. This article presents the knowledge, dispositions, and ideas of around 1, 300 indigenous and non-indigenous university students in New Zealand about learning te reo Māori as public policy. The article analyses the students' level of agreement to a series of propositions about language acquisition policy, and the epistemic and dispositional stances they took in their free-text commentary to describe the rationale for learning te reo Māori, how and where acquisition occurs, who should learn the language and to what extent, what policy should deliver, and what policy changes are needed. The article concludes that the knowledge and dispositions of the students are at odds with government policy and traditional tenets of language revitalisation theory.